2022
DOI: 10.1177/09544054221135484
|View full text |Cite
|
Sign up to set email alerts
|

A novel reciprocating cluster magnetorheological polishing device: Design and investigation of removal model

Abstract: In the traditional magnetorheological polishing of flat planar elements, there have been problems like low efficiency and uneven surface. To improve the surface quality of optical glass and explore the material removal mechanism, a novel reciprocating cluster magnetorheological polishing (MRP) device was designed with a magnetic field consisting of six curved permanent magnets and one static magnetic finite element for analysis. By analyzing the forces and motion behaviors of single abrasive particles during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Zhao et al 20 proposed a new polishing tool (bonnet) to polish freeform surface using revised Archimedes spiral polishing path to avoid the issue of under polishing and over polishing and observed that finished surface had fewer dents and bulges caused due to unpolished scratches and areas. Lu et al 21 proposed a new reciprocating cluster MR polishing device to polish K9 glass using six curved permanent magnets in MRF process and proposed a model for material removal. It was observed that surface roughness of 2.7 nm was achieved using the proposed MR device.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 20 proposed a new polishing tool (bonnet) to polish freeform surface using revised Archimedes spiral polishing path to avoid the issue of under polishing and over polishing and observed that finished surface had fewer dents and bulges caused due to unpolished scratches and areas. Lu et al 21 proposed a new reciprocating cluster MR polishing device to polish K9 glass using six curved permanent magnets in MRF process and proposed a model for material removal. It was observed that surface roughness of 2.7 nm was achieved using the proposed MR device.…”
Section: Introductionmentioning
confidence: 99%